EFFECTS OF SELF MONITORING AND MANAGEMENT STRATEGY ON VIOLENT BEHAVIOURS AMONG SENIOR SECONDARY SCHOOL STUDENTS WITHIN BIDA EDUCATIONAL ZONE OF NIGER STATE - Umaru, Y. (Sokoto Educational Review, 2019)
The study examined the Effect of Self-monitoring and Management Strategy on Violent Behaviour among senior secondary School Students. It was guided by two research questions and two hypotheses. A non-equivalent control group Quasi-experimental design involving one treatment and one control group was adopted. A total of 43 senior secondary schools (SSII) classes with high record of Behavioural problems in School within Bida Educational Zone o f Niger State were used for r the study. The instrument used for the study was the Adolescent Behavioural Assessment (ABA) which was validated by experts and used for data collection. Mean, Standard deviation and Analysis of Covariance (ANCOVA) was used to analyze the data collected. The results suggested that the use of self-monitoring and management strategy are efficacious in reducing violent behaviours in schools. Based on the findings, the introduction of peace education in schools to curb the effect of violent behaviour on academic and social development and school psychologist or counsellors’ training on the new strategies to reduce violent behaviour in school are among the recommendations proposed by this study.